Does Organizational Commitment, Ethical Leadership And Ethical Climate Affect On Deviant Behavior In The Workplace? - Akmal, Akmal; Azliyanti, Elfitra; Rosha, Zeshasina (CV. ITTC INDONESIA, 2024)
Nowadays, ethical issues in organizations are an interesting topic to discuss, especially for the problem of deviant behavior. Therefore, this issue is a major concern in the field of organization and business. Deviant behavior will have negative implications for individuals, groups, and organizations which encourages practitioners and academics to pay more attention to ethical management. The paper explores the relationship between ethical leadership, ethical climate, organizational commitment, and deviant behavior. The respondent of this research are employees of PT. Japfa Comfeed Indonesia . The study measures ethical climate using 5 indicators with 26 statement items sourced from Cullen (1993), organizational commitment using 3 indicators with 18 statement items sourced from Meyer, Allen, and Smith (1993), and ethical leadership using 10 indicators with 15 statement items sourced from Yulk (2010). The data collection method used in the research is a questionnaire sent via Google Form. Data analysis using the Partial Least Square (PLS) approach using the help of the SmartPLS program. Overall, the study suggests that promoting ethical leadership and creating a positive ethical climate can enhance organizational commitment and reduce deviant behavior at PT. Japfa Comfeed Indonesia.